The Influence of Profitability and Liquidity on Closing Stock Prices of Cigarette Companies on The Idx For The Period 2018 - 2023 - Agusandhya, Nabila; Alfiana; Mulyono (Bulletin of Management and Business, 2025)
The cigarette industry in Indonesia continues to grow and makes a significant contribution to state revenues. However, strict regulations such as increased excise rates, advertising bans, and negative sentiment towards cigarette consumption can affect the profitability and stock prices of companies in this sector. This study aims to analyze the effect of Return on Assets (ROA), Return on Equity (ROE), Net Profit Margin (NPM), Current Ratio (CR), and Quick Ratio (QR) on the stock prices of cigarette sub-sector companies listed on the Indonesia Stock Exchange (IDX) in the period 2018-2023. The research method used is a quantitative approach with multiple linear regression analysis using IBM SPSS The results of the study show that ROA has a significant positive effect on stock prices, ROE has a significant negative effect on stock prices, NPM has a significant negative effect on stock prices. Meanwhile, CR and QR do not have a significant effect on stock prices. Simultaneously, the five variables have a significant effect on stock prices. These findings indicate that profitability, especially ROA, is the main factor considered by investors in assessing cigarette company stocks, while liquidity is not a major concern. This research provides insight for investors and company management regarding the importance of asset and profit management strategies to maintain the attractiveness of shares in the capital market.